A Case Report of Multifocal Epithelial Hyperplasia (Heck's Disease) Treated with CO2 Laser - Javad Sarabadani; Sahar Heydari; Amirreza Mashreghi; Niloofar Poornazari (Mashhad University of Medical Sciences, 2017)
Focal epithelial hyperplasia or Heck's disease is a rare benign lesion of oral mucosa caused by human papilloma virus especially subtypes 13 and 32. The disease is predominantly found in children and adolescents with indigenous heritage. This paper reports a unique case of Heck's disease in an 11-year-old Iranian girl with multiple, bilateral and elevated lesions on the buccal and labial mucosa. The lesions had persisted for a year. The disease was diagnosed as focal epithelial hyperplasia through the clinical examination. Considering esthetic and functional problems, CO2 laser (Wavelength: 10600 nm) surgery was determined as a suitable choice of treatment. The patient was followed up over 1 year with no signs of lesion recurrence.